Analisis performa mesin oily water separator tipe CYF-1.OY pada pembangunan kapal baru 2000 GT dengan metode eksperimen - Budi Utomo; Sulaiman; Sunarso Sugeng; Mohd Ridwan; Samuel Febriary Khristyson (Jurnal Teknik Mesin Indonesia, 2022)
For the ideal operation of the oily water separator, maintenance and repairs should be carried out regularly so as not to interfere with the operation of the ship. The purpose of this article is to analyze the performance of the Oily Water Separator engine type CYF-1.OY on the 2000 GT ship building project. Experiment method used to determine the performance of the machine and assuming evaluation correction approach. The result of engine performance, time the machine works is directly proportional to the volume of waste capacity so that the more volume, the longer it takes depending. The efficiency is similar, meaning that the results are below 5% and are still in relevance. In operating and adjusting the Oily Water Separator, more observation and attention is needed, especially for the display and capacity of the machine.